Physycal properties of soil and yield of soybeans in corn braquiaria consortium - Chioderoli, Carlos A. [UNESP]; de Mello, Luiz M.M. [UNESP]; Grigolli, Paola J. [UNESP]; Furlani, Carlos E.A. [UNESP]; Silva, José O.R. [UNESP]; Cesarin, André L. [UNESP] (FapUNIFESP (SciELO), 2012)
In tropical regions, due to high rates of decomposition of the organic material, one of the problems for the maintenance and no tillage system sustainability is the necessity of production of great quantities of straw. With the objective to identify, in the pasture-agriculture integration system, the variations of soil physical attributes and yield of soybean on brachiaria straw, the present work was conducted at the FEPEUNESP of Ilha Solteira, SP. The randomized block experimental design was used, with nine treatments in the fatorial scheme 3x3, with four repetitions. The treatments consisted of three species of brachiaria and a consortium of the three types of brachiaria with corn. The physical properties of soil were determined before the installation of the experimente, after the harvest of corn intercropped with forage and after the harvest of soybeans. In summer the soybean crop was sown on the straw of corn and brachiaria spaced 0.45 m, with 14 lines per plot and area for data collection consisting of 4 lines of 5 m each. The results showed that intercropping and sequence of crops provided increase of soil macroporosity and total porosity. Brachiaria brizantha sown at the time of top-dressing of corn and Brachiaria decumbens sown in line promoted higher yields of soybeans.
Atributos físicos do solo e produtividade de soja em sistema de consórcio milho e braquiária
Keywords: Covering of the ground; Intercroping crops; Simultaneous sowing; Straw